Pelatihan Bantuan Hidup Dasar Petugas Tata Kelola dan Pemuda Gereja Paroki Santo Fransiskus Asisi Tebet - Sidarta, Erick; Dwiana, Alya; Sukianto, Louise Audrey; Kasvana, Kasvana; Tan, Nikita (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Sudden cardiac arrest is a condition that occurs quite frequently. This sudden cessation of heart function is caused by the loss of electrical activity in the heart, which results in the cessation of blood circulation throughout the body. Quick and proper handling of this condition can reduce the mortality rate due to cardiac arrest. Therefore, Basic Life Support (BLS) training needs to be conducted to educate the general public. The BLS training conducted for the management officers and youth of Saint Francis of Assisi Church in Tebet was carried out by providing theoretical and practical BLS lessons, as well as conducting pre-tests and post-tests to assess the participants' understanding of the material and practices provided. From the activity conducted, a total of 22 participants attended the BLS training, and there was a significant difference in the average pre-test and post-test scores. It can be concluded that the training provided was effective in increasing the participants' understanding and knowledge of BLS.